The Cognitive Differences between the Teachers and Students in the Emergency Professional Skills Training Program of Standardized Residency Training - LYU Baopu, LIU Liang, XIAO Hao, GONG Yu, MENG Qingbing, GAO Hengbo, TIAN Yingping, YAO Dongqi (Zhongguo quanke yixue)
Background Standardized residency training in emergency medicine is crucial for a high-quality clinical physician workforce. As a frontline dedicated to the treatment of ill patients, the emergency medicine serves as a critical training ground for exemplary resident. Medical skills training is an integral component of residency education, and emergency medicine core skills training numerous modules. However, in the of specific training modules between the teachers and students can impact the training's efficacy and quality. Objective To investigate and analyze the cognitive differences between teachers and residents of emergency professional skills training in standardized resident training in Hebei Province. Methods On 18 October 2021, a total of 103 teachers and residents from 15 emergency bases in Hebei Province who were prepared to participate in the standardized training skills competition for residents were selected, including 37 teachers and 66 residents. According to the "Clinical Skill Operation Refinement Process and Scoring Criteria", an electronic questionnaire was developed for 13 emergency core skill training projects according to the operation steps of the refinement process, and the scores were divided into "difficulty degree" and "omission during operation". Results In terms of "difficulty", teachers and students exhibited differing of for seven gram (53.85%) : electrocardiography, arterial puncture, abdominal puncture, single-chamber cardiopulmonary (CPR), central venous puncture, tracheal intubation, and three-cavity-two-lung tube placemen, the cognitive differences were observed in 25 steps (16.45%), where teachers rated as less mark than students (P<0.05). In terms of "omissions during operation", teachers and students also differed in their cognitive of nine (69.23%) : electrocardiography, abdominal puncture, single-chamber CPR, central venous puncture, tracheal intubation, three-cavity-two-lung tube placement, lumbar puncture, noninvasive ventilation, and thoracic puncture, the cognitive differences were observed in 24 steps (15.79%) cognitive, with teachers generally a lower mark compared to students (P<0.05). There are no differences were observed between teachers and students in terms of "difficulty" and "omissions during operation" for the remaining three: pericardium puncture, cardioversion, and bone marrow puncture (P>0.05) . Conclusion This study confirmed that there are differences between teachers and trainees in the "difficulty" and "omissions in operation" of core skills training in emergency department. On the one hand, it can promote the improvement of clinical skills training curriculum, improve training efficiency, and provide methodological basis for training high-level, high-level and application-oriented medical talents. On the other hand, this study suggests that in the future similar studies on standardized training of residents, the possible differences between teachers and trainees should be taken into account in order to reflect and explore the problems related to residential training more objectively.